PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI STOP MOTION UNTUK PEMBELAJARAN BIOLOGI DENGAN APLIKASI PICPAC - Maryanti, Sri; Kurniawan, Dede trie (Jurnal BIOEDUIN, 2018)
Based on the observation, the problem in Biology learning is the students are less enthusiastic about Biology lesson because of too many theories and topics that must be memorized and remembered so its decrease their learning interest. Biology learning requires visualization of the concept in its delivery to students. The effectiveness and efficiency of learning can be improved by using innovative learning media. Therefore prospective biology teacher are required to be able to provide a varied and innovative learning media. One of the innovative learning media is Stop Motion video animation. The purpose of this study is to produce biology learning media and to know the feasibility of learning media that has been produced. The type of this research is Research and Development using ADDIE development model, this model has 5 stages namely Analysis, Design, Development, Implementation and Evaluation. But on this study we conducted only to ADD stage of Analysis, Design and Development. In this paper we describes how the process of making and assessing the feasibility of learning media in the form of stop motion video animation on biology learning made by prospective biology teachers Semester 5 Biology educational program FTK UIN Sunan Gunung Djati Bandung 2017.